Strategies for implementing an innovative circular packaging system in e-commerce : a case study of Pytlíkovna - Tichotová, Ivana Sofie (2025)
This thesis responds to the substantial environmental footprint of single-use packaging in E-commerce by developing a business plan for a returnable packaging system, illustrating a novel circular model by facilitating multiple uses and recyclability, while maintaining sustainability, economic soundness, and operational feasibility. Based on a mix of qualitative interviews and quantitative financial modeling, this thesis tests the design's feasibility under different scenarios. It offers a comprehensive proposal for the system's distribution channels, marketing communication, and economic assumptions, detailing how returnable packaging minimizes waste via a closed-loop system. It also investigates adoption barriers among online retailers and consumers and suggests overcoming them. The research aims to demonstrate that, with optimized configurations and supportive policies, this circular packaging solution can be environmentally advantageous, economically sound, and competitive.